Causal associations between the gut microbiota and multiple myeloma: a two-sample Mendelian randomization study - Zhang, Chun-Yan; Zhang, Dong; Sun, Wen-Rui; Tang, Hai-Long; Tian, Biao; Hu, Li-Hong; Hu, Wu-Yue; Gao, Ya-Ya; Li, Miao-Yu; Xiao, Wan-Ting; Gao, Shan; Gao, Guang-Xun (Frontiers in Nutrition, 2024)
Background: Previous observational studies have indicated a potential association between the gut microbiota and multiple myeloma (MM). However, the relationship between the gut microbiota and MM remains unclear. This study aimed to ascertain the existence of a causal link between the gut microbiota and MM.Methods: To investigate the potential causal relationship between gut microbiota and MM, a twosample Mendelian randomization (MR) analysis was conducted. Exposure data was obtained from the MiBioGen consortium, which provided genetic variants associated with 211 bacterial traits. MM outcome data was obtained from the FinnGen consortium. The selection of Single nucleotide polymorphisms estimates was performed through meta-analysis using inverse-variance weighting, and sensitivity analyses were conducted using weighted median, MR Egger, Simple mode, and MR-PRESSO.The results of the study demonstrated a significant positive correlation between the Genus Eubacterium ruminantium group and the risk of MM (OR 1.71, 95%CI 1.21 to 2.39). Conversely, the Genus. Dorea (OR 0.46, 95%CI 0.24 to 0.86), Coprococcus1 (OR 0.47, 95%CI 0.22 to 1.00), RuminococcaceaeUCG014 (OR 0.57, 95%CI 0.33 to 0.99), Eubacterium rectale group (OR 0.37, 95%CI 0.18 to 0.77), and Order. Victivallales (OR 0.62, 95%CI 0.41 -0.94), Class. Lentisphaeria (OR 0.62, 95%CI 0.41 to 0.94), exhibited a negative association with MM. The inverse variance weighting analysis provided additional support for these findings.This study represents an inaugural exploration of MR to investigate the connections between gut microbiota and MM, thereby suggesting potential significance for the prevention and treatment of MM.